Recognizing distinctiveness of perinatal depression from depression in non-perinatal population: an urgent call for action - Behl, Ritika (Frontiers in Public Health, 2025)
BackgroundPerinatal Depression (PND), though recognized as a public health issue in certain countries, largely remains an obscured part of healthcare systems, especially in low-middle-income countries (LMICs), which is in turn associated with multitudinal consequences. Underscoring the uniqueness of PND can facilitate change in policymaking.AimTo highlight the distinctiveness of PND from depression found in the non-perinatal population.MethodA doctoral study was conducted in India to analyze the efficacy of existing Indian health laws and policies in addressing and managing PND, and its implications for women’s rights in the country. From the findings of the study, narrative synthesis was conducted, following an inductive approach to detail and explain the multidimensional distinctiveness of PND from depression found in the non-perinatal population.ResultsBased on various factors, including diverse etiology, the significance of pharmacotherapy treatment guidelines, timing of delivery of health interventions, gender-based health needs, and intergenerational transfer of equity, PND’s uniqueness must be reflected within the health laws and policies.ConclusionNon-provision or access to or dissemination of information about PMH, and PMDs, including PND, should be regarded as an ethical and moral issue apart from the violation of human rights principles in the existing SDG era.